Pengaruh Lingkungan Kerja Dan Sarana Prasarana Kelancaran Tugas Terhadap Kinerja Pegawai Pada PT Pos Indonesia (Persero) Kota Probolinggo - Hariyanto, Moh. Fendi; Haris, R Abdul; Widayanto, Mutinda Teguh (Universitas Panca Marga, 2024)
Human resources are the most important element whose function and role cannot be replaced by other resources, whose needs must be met properly and supported by a good and adequate work environment and infrastructure. Knowledge, experience and expertise in certain fields can influence career development for employees. One of the factors that influences employee performance is the work environment and infrastructure for the smooth running of tasks. This research aims to determine the influence of the work environment, infrastructure on the smooth implementation of tasks on employee performance simultaneously and partially on employee performance. This research method is quantitative with an associative approach. The population of this study was all 104 employees, consisting of 44 permanent employees and 60 non-permanent employees. The data collection technique uses saturated sampling. The sample consisted of 104 respondents. Data was collected through questionnaires. Data analysis techniques include validity testing, reliability testing, classical assumption testing, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results of the research show that the work environment and infrastructure on the smooth running of tasks simultaneously and partially have a significant and significant effect on employee performance.